DAYA KONSUMSI BELALANG KEMBARA (Locusta migratoria manilensis Meyen) TERHADAP TANAMAN JAGUNG (Zea mays L.) DAN SUMBANGANNYA PADA PEMBELAJARAN BIOLOGI SMP - Fuji Hutami Ningsih; Zainal Arifin; Riyanto Hamid (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2018)
Research of the power consumption of migratory locust (Locusta migratoria manilensis Meyen) to the corn crop (Zea mays L.) has been done. This research was aimed to find out the information the power consumption of migratory locust (Locusta migratoria manilensis Meyen) with difference number of individuals and eating of time. This research used experimental method with factorial completely rendomized design which consists of two factor was number of individuals (A), 1 migratory locust (A1), 15 migratory locust (A2), 30 migratory locust (A3) and eating of time, morning (B1), afternoon (B2), and evening (B3), with 9 combination of treatment which repeated three times. The data analyzed by ANAVA and BNT test. The result showed that was significant effect the power consumption of migratory locust on some parameter of observation that is difference of body weight and leaf area eaten. The interaction between the number of individuals and eating of time significantly effect the parameter of leaf area eaten, but no significant effect on the parameter of the difference in body weight. The treatment of individual number of 30 head and the evening (A3B3) had a real effect the power consumption of migratory locust on on all parameters. The information of this study hopefully can be an alternative of contextual learning in Biology lesson on Junior High School grade eight, Semester 2 on Basic Competence 3.7 and Basic Competence 4.7 about interaction of living organisms with their environment.